Bowel obstruction in obturator hernia: A challenging diagnosis. (2018) - Conti, L.; Baldini, E.; Capelli, P.; Capelli, C.
Highlights: Obturator hernia is a rare entity; delayed diagnosis and treatment are associated with high rate of morbidity. It usually occurs in female and presents with bowel obstruction symptoms such as nausea, vomit and hydroelectrolyte imbalance. Surgery is the unique treatment: both laparoscopic transabdominal or laparotomic approaches are proposed. Abstract: Introduction: The obturator hernia is a rare pelvic hernia that often comes in the shape of bowel obstruction caused by the presence of an intestinal segment, more often ileum, passing trough the obturator foramen of the pelvic wall (Fig. 1). This type of hernia accounts for 0.5-1.4% of all hernias. Case presentation: We report the clinical case of a 84-year-old woman with no previous surgical interventions, who went to the emergency room complaining of vomit and nausea, bowels closed to gas and stool, which she had experienced for three previous days. Routine blood test showed impaired renal function and hydrohelectrolyte imbalance. A CT scan revealed a right ileal, strangulated obturator hernia. The patient underwent an emergency surgical intervention with laparoscopic trans -abdominal peritoneal approach (TAP): after the reduction of the herniated segment, a primary suturing of the parietal defect was performed without ileal resection. Discussion: Because of the non-specific symptoms the diagnosis of this kind of hernia is often unclear; female are 6–9 times more likely than men to be subject to the aforementioned pathology, mostly occurring in multiparous, emaciated, elderly woman so it is also called "the little old lady's hernia". Risk factors are loss of weight, chronic pulmonary disease and ascites which increase the abdominal pressure. An unfrequent presenting sign is a palpable mass, or the Howship-Romberg sign- a pain radiating from the inner tigh and knee − but it could be misleading when confused with symptoms of gonarthrosis or lumbar vertebral disc pathology. CT scan has superior sensitivity and accuracy with respect to other radiological exams to assess the presence of an obturator hernia. Conclusion: Obturator hernia is a rare type of hernia due to his diagnosis, which is often unclear; a prompt suspect based for the non-specific symptoms is crucial for the diagnosis. Surgical management depends on early diagnosis and it is the only possible treatment for this pathology.